2020
DOI: 10.7554/elife.58246
|View full text |Cite
|
Sign up to set email alerts
|

Complementary α-arrestin-ubiquitin ligase complexes control nutrient transporter endocytosis in response to amino acids

Abstract: How cells adjust nutrient transport across their membranes is incompletely understood. Previously, we have shown that S. cerevisiae broadly re-configures the nutrient transporters at the plasma membrane in response to amino acid availability, through endocytosis of sugar- and amino acid transporters (AATs) (Müller et al., 2015). A genome-wide screen now revealed that the selective endocytosis of four AATs during starvation required the α-arrestin family protein Art2/Ecm21, an adaptor for the ubiquitin ligase R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 99 publications
(217 reference statements)
2
61
0
Order By: Relevance
“…The interaction with ARRDC3 promotes retention of the β2AR on endosomes by preventing its association with the sorting nexin family member 27 (SNX27), which mediates recycling of β2AR back to the plasma membrane [Temkin et al., 2011; Tian et al., 2016]. The crystal structure of the N‐terminal lobe of ARRDC3 revealed a large electropositive region (‘basic patch’), which seems to be important for β2AR binding [Qi et al., 2014a], similar to the proposed/putative mechanism of substrate binding in several yeast ARTs [Guiney et al., 2016; Ivashov et al., 2020] and β‐arrestins [Mayer et al., 2019].…”
Section: Trafficking Functions Of Other Arrdcsmentioning
confidence: 92%
See 2 more Smart Citations
“…The interaction with ARRDC3 promotes retention of the β2AR on endosomes by preventing its association with the sorting nexin family member 27 (SNX27), which mediates recycling of β2AR back to the plasma membrane [Temkin et al., 2011; Tian et al., 2016]. The crystal structure of the N‐terminal lobe of ARRDC3 revealed a large electropositive region (‘basic patch’), which seems to be important for β2AR binding [Qi et al., 2014a], similar to the proposed/putative mechanism of substrate binding in several yeast ARTs [Guiney et al., 2016; Ivashov et al., 2020] and β‐arrestins [Mayer et al., 2019].…”
Section: Trafficking Functions Of Other Arrdcsmentioning
confidence: 92%
“…Further metabolic cues can induce the selective endocytosis of a wide range of nutrient transporters independently of substrate binding. Amino acid and nitrogen limitation, for example, triggers endocytosis of Mup1 and Can1, but requires the action of Art2 [Jones et al., 2012; Müller et al., 2015; Ivashov et al., 2020] (reviewed in [Babst, 2020]). The predicted arrestin domain of Art2 contains a C‐terminal basic motif, which directs Rsp5 to an acidic patch in the C‐terminal tails of Mup1 and Can1 (Figure 1B, lower panel).…”
Section: Principles Of Substrate Recognition By Art–rsp5 Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no clearly defined mammalian ortholog of Git1, it has been shown that the mammalian glucose transporter Glut2 can uptake GPI and is considered functionally analogous (Mariggio et al ., 2006). The trafficking of the other transporters needed for inositol uptake, such as Itr1 and Itr2, and members of the related glucose transporter family, including Hxt1, Hxt3, and Hxt6, are each controlled by a family of protein trafficking adaptors known as the α-arrestins (Nikko and Pelham, 2009; Harada et al ., 2010; O’Donnell et al ., 2015; Hovsepian et al ., 2017; Ivashov et al ., 2020). We therefore sought to determine if the α-arrestins might similarly play a role in Git1 transporter trafficking, whose removal from the cell surface was previously linked to clathrin-mediated endocytosis and subsequent vacuolar degradation (Almaguer et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The α-arrestins, conserved from yeast to man, act as bridges between membrane proteins (referred to as cargos) and Rsp5, a ubiquitin ligase known to regulate the endocytosis of many nutrient permeases; the ortholog of which is Nedd4-2 (Rotin and Kumar, 2009). Internalization of many nutrient transporters, such as the Fur4 uracil permease, and the Mup1 methionine permease, can be triggered by the presence of excess substrate (i.e., uracil or methionine, respectively) and subsequent ubiquitination of these transporters by Rsp5 ensures their interaction with the endocytic machinery, many components of which have ubiquitin-interaction motifs (Blondel et al ., 2004; Lin et al ., 2008; Nikko and Pelham, 2009; Ivashov et al ., 2020). Modification of cargos by even a single ubiquitin is often sufficient to induce internalization (Shih et al ., 2000; Raiborg et al ., 2002; Stringer and Piper, 2011).…”
Section: Introductionmentioning
confidence: 99%